The analysis of organizational culture using the organizational culture assessment instrument (ocai) based on the competing values framework (cvf) case study: corporate human resource (chr) directorate kompas gramedia - Sandrisha, Mahacita; Budi Saksono, Prasetyo (The Indonesian Journal of Business Administration, 2019)
Abstract. Organizational culture becomes one of the important factors in determining success of a company achieving its goals. This research is aimed to figure out what the current and expected culture at CHR Kompas Gramedia, and give recommendation based on the gap between current and preferred culture. The objectives will be achieved by doing quantitative data analysis with questionnaires by using the Competing Values Framework based on six dimensions of organizational culture using Organizational Culture Assessment Instrument (OCAI) to all CHR Kompas Gramedia employees with the total population of 67 people. The questionnaire contains eight statements in each dimension, which are divided into four current cultural statements and four expected cultural. The overall organizational culture that is dominated in the CHR Kompas Gramedia is the hierarchy culture with 28.12 points. The clan culture gets the lowest culture with a total of 23.70 points. In the next three years, this organization expects a culture that is inclined to be dominated by clan culture with a number of 32.10 points, by reducing the hierarchy culture by the amount of 18.66 which is currently embedded in the company. Hence, CHR Kompas Gramedia can conduct training such as mindfulness, personal transformation coaching training, team building-learning, bottom-up approach, and propose new service innovation.Keywords: organizational culture, OCAI, CVF, clan, adhocracy, market, hierarchy